Anorectal Autoeroticism: A Case Report - Tulachan, Pratikchya; Shrestha, Kenison; Chapagai, Manisha; Dhungana, Saraswati; Pant, Sagun B; Lama, Pratik; Bhandari, Ramesh S (Journal of Institute of Medicine Nepal, 2019)
Anorectal autoeroticism is one kind of paraphilia where individual attains sexual pleasure through self inserting objects into ones rectum. We present here a case of 40 years old man presented in Surgery department with retention of steel glass into his rectum which he had inserted himself to achieve sexual satisfaction.